Real-time simulation and performance analysis of multimachine power systems using dSPACE simulator. (January 2016) - Ramya, R; Selvi, K; Murali, K
The analysis of the characteristics of multiple machines constituting a power system in real time is of paramount importance. The reported work uses dSPACE, a dynamic simulator, in investigating the characteristics of the said multimachine system. The transient model of the Western System Coordinating Council (WSCC) nine-bus, three-unit system is developed using MATLAB/Simulink. Using real-time interface, the model is executed in the digital signal processor (DSP) of dSPACE hardware. The model is analyzed for its performance against multiple changes in mechanical torque and load variation. The transient behavior of the model upon incidence of a significant network fault and its robustness towards to perturbations in network and system parameters are thoroughly analyzed. The conditions are emulated by usage of the digital signal processor and DS1104 Controller Board.